Analisis Teknik dan Uji Kinerja Mesin Peniris Minyak (Spinner) (Technical Analysis and Test Performance of Oil Spinner Machine) - Wahyu K Sugandi; Ade Moetangad Kramadibrata; Fetriyuna Fetriyuna; Yoga Prabowo (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
Technical specification of the spinner at the Pilot Plant of FTIP Unpad was needed to be reviewed through technical analysis and performance test. Experimental Design method of the research was carried out by on the spot observations, measurements, and recalculating machine main components. Results obtained from technical analysis showed that the machine required a driven power of 216 W, one single belt, a minimum shaft diameter of 16 mm, as well as a pin diameter at the main roller and at the pulley of 5,46 mm and 6 mm, respectively. It had a deflection torsion of 0,0460 a critical shaft speed of 1338 RPM, a bearing life of 3.227.817,96 hours, a frame deflection of 0,24 mm, and a frame welding load of 503,74 N. Sofar, the machine has fulfilled its technical feasibility. While the results of performance tests showed that the best taste sensation of the crackers was termed at an engine speed of 650 rpm at an actual capacity of 3.6 kg/h and at a power of 120 W, a specific spin energy of 120 kJ/kg, a spin yield of 97.38 %, an engine efficiency of 65.60 %, an engine performance index of 0.95 at a level of noissiness of 86.86 dBA. The data has fulfilled the performance requirement, but due to its vibration frequency of 21.44 mm/s – which was dangerous, improvements related to it had to be done. Keywords: technical analysis, oil spinner, performance test ABSTRAK Spesifikasi teknis mesin peniris minyak (spinner) di laboratorium Pilot Plant FTIP UNPAD perlu dikaji-ulang melalui analisis teknik dan uji kinerja. Metode analisis deskriptif dalam penelitian ini dilakukan melalui pengukuran, pengamatan dan perhitungan terhadap komponen-komponen utama mesin. Hasil analisis teknik menunjukkan bahwa untuk mengoperasikan mesin ini dibutuhkan daya penggerak 216 Watt, satu sabuk, diameter poros minimum 16 mm, defleksi puntiran 0,0460, putaran kritis poros 1338 RPM, diameter pin pada motor penggerak 5,46 mm, diameter pin pada roll utama dan diameter puli 6 mm. Sementara umur bantalan 3.227 jam, lendutan rangka 0,24 mm, dan beban las rangka 503,74 N. Secara teknis mesin ini telah memenuhi kelayakan teknis. Hasil uji kinerja mesin menunjukkan bahwa sensasi rasa kerupuk terbaik diperoleh pada kecepatan putaran motor 650 RPM dengan kapasitas aktual 3,6 kg/jam pada daya 120 Watt, energi spesifik penirisan 120 kJ/kg, rendemen penirisan 97,376 %, efisiensi mesin 65,60 %, indeks performansi mesin 0,95, dan tingkat kebisingan 86,86 dBA. Data ini telah memenuhi spesifikasi kinerjanya. Namun dengan frekuensi getaran 21,44 mm/s (berbahaya). Perbaikan teknis terkait masalah ini masih perlu dilakukan. Kata kunci: analisis teknik, mesin peniris minyak, uji kinerja